Intercultural Communication between Colombian and American Teachers in Colombian Institutions - Georgia Costalas (Profile: Issues in Teachers' Professional Development)
This article, which is based on observations from working in multicultural environments for twenty- five years and a review of sources on intercultural communication, addresses the intrinsic difficulties that arise from communication among people of different cultures. The connection between language and culture is so close that communication among internationals creates challenges of intercultural communication even when communicating in the same language. In Colombia, especially in institutions that teach English, there are bicultural or multicultural groups of teachers that work together. Some misunderstandings arise because of an inadequate understanding of colleagues’ values systems. This article includes three common work situations, the possible problems arising from inappropriate communication and some suggestions for overcoming intercultural communication difficulties.